Penyuluhan Literasi Uang Digital Bagi Siswa SMA Muhammadiyah 8 Cerme Gresik - Heru Baskoro; Ahmad Qoni Dewantoro; Sukaris Sukaris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Currently, technological developments are accompanied by the development of digital money, therefore a complete understanding of digital money needs to be known by all people, including students at the secondary level, including SMA Muhammadiyah 8 Cerme. The problem that occurs in SMA Muhammadiyah 8 Cerme students is that some students do not yet have a comprehensive understanding of digital money, its urgency, benefits and its relation to business, so digital money literacy needs to be socialized. The method used in this activity was outreach to 70 students of SMA Muhammadiyah 8 Cerme. This activity has several. The expected output is that the participants' knowledge increases. The method used is the socialization method through in-class seminars. The result of this service activity is that the participants can find out about the concepts of digital money, have been able to understand the various types of digital money, have a wise awareness in using digital money and the participants can associate digital money with the business to be carried out, and can see business opportunities with digital money.